"KOPI NGAJI”: BUILDING A HOLISTIC VILLAGE COMMUNITY DEVELOPMENT MODEL BASED ON ISLAMIC VALUES - Setiawan, Achdiar Redy; Mukti , Beta Pujangga (Airlangga International Journal of Islamic Economics and Finance, 2023)
Since the enactment of Law Number 6 concerning Villages, there has been a shift in the development paradigm in the village as the smallest administrative unit in the Indonesian constitutional structure. The village is no longer the object of development, but the village is placed strategically as the subject of development. Village development should not be carried out partially. Villages and their communities need to be developed comprehensively, covering all aspects of their whole humanity. The purpose of this research is to uncover and describe one model of holistic village community development, namely "KoPi Ngaji", which has been implemented in Bodeh Village, Yogyakarta. "KoPi Ngaji" is a program in the religious sector in green open spaces that aims to instill rational thinking, emotional feelings, and spiritual inner as well as empower the economy of the local village community. This research uses a qualitative approach with case study data analysis. This study found that the "KoPi Ngaji” program is a holistic village community development model based on Islamic values. The "KoPi Ngaji" platform is run with a 3H approach (Heart, Head, and Hands). Starting with strengthening the Islamic spiritual mentality, this program then builds the economic power of the community through strengthening narratives reasoning, a sense of creativity, and the ability to take action for change.